Pelatihan Pemanfaatan Bahan Alam di Lingkungan Sekolah Untuk Praktikum Biologi di Tigkat SMP/SMA - Purnamasari, Vita; Sujarta, Puguh; Suyono, Ignatius Joko; Farmawaty, Farmawaty; Yuliana , Yuliana (Bakti Hayati: Jurnal Pengabdian Indonesia, 2023)
Practical activities are part of teaching which aims to give students the opportunity to test and implement in real situations what is obtained in theory. The use of natural materials in the school environment, apart from having cheap capital, has a big advantage, namely getting to know the school environment closely. The aim of this service activity is to provide provisions for biology teachers in SMP/SMA. Community Service will be held on July 15 2023. Participants will be SMP/SMA of the biology teachers in the MGMP area of Keerom Regency. The activity method uses lecture, discussion and simulation methods in practice. The results of the activity showed that the activity participants were very enthusiastic and able to utilize natural materials in the school environment in biology practicum activities.